Association of Toll‐like Receptor 4 Gene polymorphisms with susceptibility to type 2 diabetes mellitus in the Chinese population Toll样受体4基因多态性与中国人群2型糖尿病易感性的关联研究. (3rd October 2014) - Peng, Danfeng; Jiang, Feng; Zhang, Rong; Tang, Shanshan; Chen, Miao; Yan, Jing; Sun, Xue; Luo, Yi; Hu, Cheng; Jia, Weiping
Abstract Background Toll‐like receptor 4 (TLR4) plays an important role in innate immunity. Activation of innate immune response and subsequent chronic low‐grade inflammation are thought to be involved in the pathogenesis of type 2 diabetes. In this study, we aimed to investigate the association of TLR4 variants with type 2 diabetes in the Chinese population. Methods Seven tag single nucleotide polymorphisms (SNPs) of TLR4 based on HapMap Chinese data were genotyped in the Shanghai Chinese, including 3404 type 2 diabetes patients and 3401 controls. The controls were extensively phenotyped for the traits related to glucose metabolism and insulin secretion. Results In total participants, we identified that rs10759932 and rs1927911 were associated with type 2 diabetes (odds ratio 1.106, P = 0.009 for rs10759532, odds ratio 1.092, P = 0.013 for rs1927911). rs11536889 showed a trend association with type 2 diabetes (odds ratio 0.957, P = 0.057). This SNP was also associated with 2‐h plasma glucose (P = 0.033) and high‐density lipoprotein‐cholesterol (P = 0.031). In female participants, rs10759932, rs1927911 and rs11536889 were associated with type 2 diabetes (odds ratio 1.176, P = 0.002 for rs10759932, odds ratio 1.136, P = 0.009 for rs1927911, odds ratio 0.882, P = 0.024 for rs11536889). Besides, rs11536889 was significantly associated with 2‐h plasma glucose (P = 0.050) and HOMA‐B (P = 0.046) with adjusting for age and body mass index in female normal subjects. Conclusions We conclude that genetic variants of TLR4 are associated with type 2 diabetes in the Chinese population, especially in female subjects.